Critical Water Activity for the Preservation of Lactobacillus bulgaricus by Vacuum Drying - Tymczyszyn, Emma Elizabeth (2008)
Lactobacillus delbrueckkii subsp. bulgaricus was dried under vacuum at different temperatures and its preservation evaluated following three parameters: lag time, percentage of membrane damage and z potential).  Microorganisms were dehydrated at 30, 45 and 70 ºC in a vacuum centrifuge for different times. The water activity (aw) achieved at each time of drying for the temperatures of dehydration were correlated with the cell recovery evaluated by means of: a) kinetics of growth in milk after drying, as measure of the global damage; b) quantification of the membrane damage using the fluorescent dyes SYTO 9 and PI.; c) determination of changes in the superficial charges (z potential) as measured of the increase in the hydrophobic residues exposed in the bacterial surface after dehydration. The dyes are able to penetrate healthy bacterial cells. The difference is that SYTO 9 generally labels all bacteria in a population (those with intact and those with damaged membranes) whereas, PI penetrates only when bacterial membranes are damaged, causing a reduction in the SYTO 9 fluorescence when both dyes are present. These changes correlate well with the bacterial damage occurred during the dehydration process. The standardization of the vacuum drying process was done by applying the Page´s model by the determination of parameters k (drying rate constant) and n (drying time index) for different conditions. The fitting of the plot aw vs time of drying allows the determination of dehydration parameters in appropriate time-temperature ratios in which no cell damage occurs. The evaluation of three parameters of damage (lag time, percentage of membrane damage and z potential) allowed us to conclude that at the lowest temperature of dehydration, cell membrane damage is not crucial for the bacterial recovery after rehydration. The slow leak out of non-bound water occurs and the first target of damage is the as are the increase in the lag time and the changes in the zeta potential, as was observed for microorganisms dehydrated at 45 and 70 ºC for larger times.